Clinical study of feto-maternal outcomes in cases of gestational diabetes mellitus - Rathod, Jalpa K.; Vohra, Hafsa M.; Vasava, Jagruti V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To study of prevalence of gestational diabetes mellitus in the community, demographic parameters like age, gestational age at diagnosis, parity, complications related to gestational diabetes mellitus, and plan the management of gestational diabetes mellitus and to reduce the maternal and perinatal morbidity and mortality. Methods: In this prospective observational study we included 50 patients with gestational diabetes mellitus were studied for feto-maternal outcome. The study was conducted from October 2018 to October 2020 at department of Obstetrics & Gynaecology, B. J. Medical college and Civil Hospital, Ahmedabad. Results: Total 50 cases of gestational diabetes mellitus were studied. It was observed that gestational diabetes mellitus were more common in elderly age group (60%), multigravida patients wer more commonly involved (48%). Past history of gestational diabetes melllitus was present in 42.2% of cases, 74% of cases required insulin for glycemic control,64% cases required delivery by caesarean section, maternal complications like preeclampsia (10 cases), polyhydramnios (22), uteroplacental insufficiency (4), macrosomia, sudden intrauterine death (3) and operative delivery were more common. 6 neonates developed respiratory distress syndrome, 10 developed hypoglycemia, and 13 neonates required NICU admission, 6 neonates underwent perinatal mortality. Conclusions: Gestational diabetes mellitus has become a global public health burden. Gestational Diabetes Mellitus is one of the leading causes of morbidity and mortality for both mother and infant worldwide. Early detection of gestational diabetes mellitus, timely referral, frequent antenatal visits, management of the identified cases at tertiary centres can lead to decreased maternal and fetal morbidity and mortality.